Resíduo da torrefação do café como fonte de potássio no cultivo do girassol - Moura, Maria da Conceição Freitas (2016)
In view of the sunflower crop multiple utilities, such as raw material for production of biofuels, feed animal, products for aesthetic and health, as well as use in the crop rotation system and the interference of this fertility and cycling of soil nutrients, observed its importance as a culture that deserves to be cultivated by farmers. The coupled use of organic materials in the soil, combined with the positive characteristics of the sunflower crop, enables minimize production costs by reducing the purchase of chemical fertilizers and adding beneficial features to the soil, thus, the organic fertilizer by use of agroindustrial residue deserves to be studied, especially in the currentness, because is growing environmental problems due to the management and overuse of chemicals deposited on the soil. Research should be conducted with agroindustrial alternatives to analyze its efficiency on crops and conditions offered to the soil and the environment, by the reduction of chemical fertilizers and the inappropriate disposal of this residue in nature, minimizing soil pollution. This research aimed to evaluate the physiological and biochemical characteristics of sunflower cultivars, and the agronomic characteristics and production components as also influence of organic residue on the physiological quality of sunflower achenes. The treatments are contained in a factorial with additional control (2x4+2), where 2 are the cultivars (BRS 122 e BRS 323), 4doses K of the organic residue (T1=0, T2=40, T3=80 e T4=120 kg ha-1) plus additional control that was the potassium chloride in the dosage of 60 kg K ha-1 for both cultivars. The data showed that for the physiological and biochemical aspects the organic residue did not affected the physiology of sunflower plants and to characteristics and production components observed that the cultivar BRS 323 had the highest number of leaves, diameter of the capitulum and productivity, while the cultivar BRS 122 showed the highest plant height and to analyze the physiology of achenes the results showed that the organic residue in the dose 0 kg K ha-1 for the first germination count and the dose 120 kg K ha-1 on the emergence of seedling relative the cultivar BRS 122 presented underperformed potassium chloride, and the emergency speed index in doses 0 and 40 kg K ha-1 for cultivar BRS 122 and the doses 0 and 120 kg K ha-1 from cultivar BRS 323. We conclude that the organic waste can be replaced by potassium chloride without negative effect on the sunflower crop.